ANALISIS ANGGARAN SEBAGAI ALAT PENGENDALIAN BIAYA OPERASIONAL - Nasution, Nurul Aini Rahmi; Amalia, Mekar Meilisa (UNIVERSITAS DHARMAWANGSA, 2023)
The study aims to analyze the budget as a means of controlling operating costs at PT Pelita Guna Lestari. The research uses secondary data which is quantitative and qualitative in nature. Data collection using interviews and documentation studies. The data analysis method used is descriptive. The results of the study found that the company has not carried out all cost controls properly, it can be observed from the existence of costs that experience unfavorable variance due to lack of supervision from management.Keyword: Budgeting, Analysis of variance, Operational cost control